Kiln-drying optimization for quality pacific coast hemlock timber. Issue 15 (18th November 2017) - Shahverdi, Mahdi; Oliveira, Luiz; Avramidis, Stavros
ABSTRACT: The pacific coast hemlock or "hem-fir" is a dominant species mix in British Columbia that is difficult to kiln-dry; hence, many mills are quite conservative with their drying schedules. Furthermore, mills tend to dry hem-fir with no green moisture content presorting, thus promoting high moisture differences within and between dried timbers. In this study, application of green chain moisture-based sorting, coupled with a modified drying schedule, was considered to be a potential way to improve drying times, moisture content spreads, and lumber quality. Modified schedules coupled to three-group green moisture content presorting, i.e., mixed, low, and high, were compared to a standard industrial one. To evaluate the process and product quality, final moisture content variation between and within lumbers, drying rates, warp, surface and internal checks, shrinkage, and casehardening were assessed. Data analysis revealed that there was no significant difference between the drying runs in terms of final moisture content variation, except in the high initial moisture content group. In regard to the sorting, high initial moisture content sorting helped to reduce the final moisture content variation. In particular, the modified schedule, when there was a high initial moisture content sorting, did improve the uniformity of final moisture content in comparison to the industrial one.